Synthetic model of a new deoxybenzoin derivative from Deguelia hatschbachii A.M.G. Azevedo - Magalhães, Aderbal Farias; Magalhães, Eva Gonçalves; Trazzi, Giordano; Valeria Regina de Souza (Eclética Química, 2005)
In this paper we describe the synthesis of 2 ́,4 ́-dimethoxy-8-(propyl-2-one)-deoxybenzoin, a new compound employed as a model for the comparison with the respective spectral data for 6’,4- dihydroxy-3’-(3,3- dimethylallyl)-2",2"-dimethylchromene(5",6":5’,4’)-2’-methoxy-8-(propyl-2-one) deoxybenzoin, recently isolated from Deguelia hatschbachii A.M.G. Azevedo. Both compounds have a “propyl-2-one” group attached to C-8 of the deoxybenzoin skeleton, for which there is no precedent in the literature. The Friedel-Crafts reaction of 1,3-dimethoxybenzene with phenylacetyl chloride furnished 2 ́,4 ́-dimethoxydeoxybenzoin, that after reaction with allyl bromide gave 2 ́,4 ́-dimethoxy-8-(allyl)- deoxybenzoin. Wacker oxidation gave the desired model compound in 15% overall yield. The corresponding spectral data reinforced the structure previously determined for the natural product.